(untitled) (Research, Society and Development, 2021)
Objective: The objective of this study is to carry out a integrative review on the use of models available on the market, addressing issues with existing studies, showing the various models available, also thinking about their efficiency and cost benefit. Methodology: A search of articles in the PubMed and Scielo databases was performed using the descriptors: simulation-based surgical training, maxillofacial and surgery, without restricting the language. Articles that did not present clarity in the methodology and that were not appropriate to the subject researched were excluded. Results: After reading the abstracts and applying the inclusion and exclusion criteria, seven articles were selected for review. The studies proved the satisfactory efficiency of the described models. Final considerations: The models facilitate training in surgical techniques, which can later reduce the operation time and lead to a better execution of skills in reality.